국내 재래종 벼 유전자원의 중배축 신장 특성 평가 - 박소연(So-Yeon Park); 장성규(Seong-Gyu Jang); 이주현(Joohyun Lee); 권순욱(Soon-Wook Kwon) (Korean journal of breeding, 2019)
Rice landrace germplasms are highly valuable because of their wide genetic variation. Their traits have not been selected by modern breeders but by nature thus those traits and the gene associated with them have tremendous potential to improve modern rice cultivars. The first step to utilize this potential is to conduct fine evaluation of the target traits to select superior germplasm for a breeding program. Here, with 386 Korean landrace germplasm, we evaluated mesocotyl elongation traits which possibly promote direct seedling cultivation in rice. Mesocotyl length ranged from 0 mm to 28 mm. Among the tested landraces, we selected and reported the top 20 performance landraces whose mesocotyl length were larger than 16 mm. The previously reported agronomic traits for the selected 20 landraces also were listed for breeders to promote utilizing these germplasms in a breeding program. KCI Citation Count: 1